Analisis Dampak Penerapan E-Filing dalam Pelaporan SPT Tahunan Orang Pribadi di KPP Pratama Bandung Cicadas - Yuni Yuni (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Taxes are a major source of government revenue used to support national development. To improve taxpayer compliance, the Directorate General of Taxes (DGT) has implemented the e-Filing system for electronic Annual Tax Return (SPT) submissions. This study aims to analyze the effect of e-Filing implementation on individual taxpayer compliance at KPP Pratama Bandung Cicadas. The research uses a descriptive quantitative approach with secondary data collected from 2020 to 2024. Data analysis was carried out using multiple linear regression with the assistance of E-Views software. The results indicate that e-Filing usage and taxpayer compliance have a significant impact on the increase in Annual SPT submissions. This indicates that the application of digital technology such as e-Filing contributes positively to improving tax administration efficiency and achieving national revenue targets.